Hot corrosion behavior of Y3Al5O12/LaPO4 materials exposed to molten V2O5. Issue 10 (15th May 2022) - Chen, Ting; Sun, Junbin; Song, Chenxi; Huang, Ling; Qi, Xiang; Wang, Juan; Xu, Zhifeng; Lu, Weihong; Chen, Xiaolong
Abstract: The current study reports the fabrication of (1- x ) Y3 Al5 O12 / x LaPO4 ( x  = 0, 0.1, 0.2, 0.3, 0.4) composites and their evaluation against molten V2 O5 corrosion at 900 °C and 1000 °C for 20 h. The phase compositions and microstructures of the samples were analysed using X-ray diffraction (XRD) spectroscopy, as well as scanning electron microscopy (SEM), both before and after the corrosion tests. The yttrium aluminium garnet (Y3 Al5 O12, YAG) was easily corroded by molten V2 O5, with the primary product being YVO4 . While LaPO4 exhibited perfect resistance to the molten V2 O5 corrosion, it was ineffective at improving the corrosion resistance of the YAG/LaPO4 composite materials. However, the LaPO4 /YAG double layers materials prepared with LaPO4 coated on the surface of YAG exhibit excellent resistance to molten V2 O5, owing to the formation of the P diffusion layer at the interface between the LaPO4 and YAG, which acts as a sealing layer, preventing the molten V2 O5 from penetrating.